1960
DOI: 10.1136/hrt.22.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Dye Dilution Curves in Congenital Heart Disease

Abstract: The need for methods capable of detecting and estimating roughly the size of congenital cardiac defects has increased with the recent rapid developments in cardiac surgery. The application of dye dilution technique to the study of these patients is largely due to the extensive work of Wood and his colleagues at the Mayo Clinic since 1950. However, although the development of these techniques represents a most valuable addition to the methods available for investigation, they are perhaps more elaborate than is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1961
1961
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…We agree with Oakley et al (1960) that right-to-left shunts may be shown up by dye dilution curves where arterial blood does not show any desaturation. As long as technically satisfactory curves can be obtained, even a very small shunt will show.…”
Section: Dye Dilution Curves and Intracardiac Shuntssupporting
confidence: 91%
“…We agree with Oakley et al (1960) that right-to-left shunts may be shown up by dye dilution curves where arterial blood does not show any desaturation. As long as technically satisfactory curves can be obtained, even a very small shunt will show.…”
Section: Dye Dilution Curves and Intracardiac Shuntssupporting
confidence: 91%
“…Other workers have confirmed these findings (Cooley et al, 1957;Gottsegen et al, 1957). The use of dye-dilution curves in our first two cases confirmed the diagnosis by showing the presence of a left-to-right shunt (Swan and Wood, 1957;Oakley et al, 1960).…”
Section: Discussionsupporting
confidence: 65%
“…Indicator dilution curves with tricarbocyanine, when recorded from the right side of the heart, provide a very accurate way to localize a left-to-right shunt Falholt and Fabricius, 1958;Oakley et al, 1960;Sanders and Morrow, 1959). With this technique, it is possible to detect a left-to-right shunt of a magnitude of 20 per cent (Fox and Wood, 1960).…”
Section: Discussionmentioning
confidence: 99%